PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI MEDIASI KOMITMEN ORGANISAIONAL PADA SEKRETARIAT DAERAH KABUPATEN PATI - Saparyati, 11 52.02 0061 (Students Journal of Economic and Management, 2013)
The purpose of this research was to analyze the employee performance of Sekretariat Daerah Kabupaten Pati. This research uses the variables of organizational culture and motivation to analyze the influence of employee performance. This study also used organizational commitment as the intervening variables to analyze the influence of the level of employee commitment to the organization. The population of this research are all the employees Sekretariat Daerah Kabupaten Pati, amounting to 221. While the sample taken in this research were as many as 126 people drawn from the population. Technical test data used in this study include validitas test, reliability test, multiple regression analysis, t test, and mediation test to verify and prove the hypothesis, The Analysis data techniques in this study use software computer program SPSS versi.16.00. program After it has been processed by this program, get the result from validity and reliability test. All variable are valid by the score of KMO and Bartlettâs Test > 0,5 and also matrix component fulfill loading factor > 0,4. All variable are reliable by the score of cronbach alpha > 0,6. The results of the first hypotheses test can be proved that theÂ show that the organization culture variables have a positive influence on the organizational commitment. The second hypotheses test variableÂ motivation have a positive influenceÂ on the organizational commitment. The third hypotheses test organization culture variable positive influence on the performance. The fourth hypotheses testÂ motivationÂ variable positive influenceÂ on the performance.Â And The five hypotheses testÂ organizational commitmentÂ variables did not effectÂ for performance.Â Strong influence of organization culture is directly compared to the performance through the mediation of organizational commitment. Moreover of motivation has strong directly influence compared toward the performance through the mediation of organizational commitment. Â Keywords : Organization culture,Â Motivation, Organizational commitment,Â Â Performance.